Retinal Prostheses: A Clinical Perspective. (May 2017) - Nazari, Hossein; Falabella, Paulo; Yue, Lan; Weiland, James; Humayun, Mark S.
Artificial vision is restoring sight by electrical stimulation of the visual system at the level of retina, optic nerve, lateral geniculate body, or occipital cortex. The development of artificial vision began with occipital cortex prosthesis; however, retinal prosthesis has advanced faster in recent years. Currently, multiple efforts are focused on finding the optimal approach for restoring vision through an implantable retinal microelectrode array system. Retinal prostheses function by stimulating the inner retinal neurons that survive retinal degeneration. In these devices, the visual information, gathered by a light detector, is transformed into controlled patterns of electrical pulses, which are in turn delivered to the surviving retinal neurons by an electrode array. Retinal prostheses are classified based on where the stimulating array is implanted (ie, epiretinal, subretinal, suprachoroidal, or episcleral). Recent regulatory approval of 2 retinal prostheses has greatly escalated interest in the potential of these devices to treat blindness secondary to outer retinal degeneration. This review will focus on the technical and operational features and functional outcomes of clinically tested retinal prostheses. We will discuss the major barriers and some of the more promising solutions to improve the outcomes of restoring vision with electrical retinal stimulation.